Monolithic and Scalable Au Nanorod Substrates Improve PEDOT–Metal Adhesion and Stability in Neural Electrodes. Issue 22 (23rd October 2018) - Ganji, Mehran; Hossain, Lorraine; Tanaka, Atsunori; Thunemann, Martin; Halgren, Eric; Gilja, Vikash; Devor, Anna; Dayeh, Shadi A.
Abstract: Poly(3, 4‐ethylenenedioxythiophene) or PEDOT is a promising candidate for next‐generation neuronal electrode materials but its weak adhesion to underlying metallic conductors impedes its potential. An effective method of mechanically anchoring the PEDOT within an Au nanorod (Au‐nr) structure is reported and it is demonstrated that it provides enhanced adhesion and overall PEDOT layer stability. Cyclic voltammetry (CV) stress is used to investigate adhesion and stability of spin‐cast and electrodeposited PEDOT. The Au‐nr adhesion layer permits 10 000 CV cycles of coated PEDOT film in phosphate buffered saline solution without delamination nor significant change of the electrochemical impedance, whereas PEDOT coating film on planar Au electrodes delaminates at or below 1000 cycles. Under CV stress, spin‐cast PEDOT on planar Au delaminates, whereas electroplated PEDOT on planar Au encounters surface leaching/decomposition. After 5 weeks of accelerated aging tests at 60 °C, the electrodeposited PEDOT/Au‐nr microelectrodes demonstrate a 92% channel survival compared to only 25% survival for spin‐cast PEDOT on planar films. Furthermore, after a 10 week chronic implantation onto mouse barrel cortex, PEDOT/Au‐nr microelectrodes do not exhibit delamination nor morphological changes, whereas the conventional PEDOT microelectrodes either partially or fully delaminate. Immunohistochemical evaluation demonstrates no or minimal response to the PEDOT implant. Abstract : A monolithic and scalable method is demonstrated for the fabrication of poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) on Au nanorod (Au‐nr) substrates, with superior mechanical and electrochemical stabilities. The reported technique to improve PEDOT:PSS electrode stability, using an Au‐nr adhesion layer, can benefit conductive polymer (CP)–based neural interfaces for chronic implants or neural stimulation applications where the long‐term stability of the CP film is critical.